Open distance learning for teachers - Kukharenko, V. M.; Oleinik, T. (My University, 2019)
The purpose of the work is to demonstrate the results of the study on the role of open education for the system of professional development (advanced training) of distance and blended learning teachers. Research Laboratory of Distance Learning (RLDL) NTU "KhPI" offers teachers of educational institutions distance courses "Introduction into distance learning", "Distance education for managers", "Technology of design distance course", "Tutor’s Practicum ", "Blended learning", "Distance Course Expertise", "Content Curator". Teachers from universities, institutes of postgraduate pedagogical education and teachers of schools of Ukraine took part in the open distance courses since 2014, more than 2,400 students have been enrolled in courses. There is presents research results concerning quality teaching and learning based on the educational technology portfolio at the KhNPU. More than 10 years of development formative assessment kit in the context of the integration of digital resources into teaching and later open educational resources into blended learning. It’s no doubt, experience shows that at the initial stage of study a majority of students are interested preferably in the technical side of digital activity in the study. Experience showed they need time for the ready to consciously use the wide possibilities of a portfolio for the development of their independent evaluation, learning reflection, critical thinking, active research position and professional identity of the teacher. In this way, we have convinced the enhancement of the educational environment aimed at taking means of the digital portfolio should be recognized among the important conditions of the quality education improvement.
Keywords: OER; OEP; open online course; personal learning environment; ADDIE; tutor; digital portfolio